Nurse specialist in family planning. - Newton, J (1976)
In an experimental clinic, run by nurse specialists in family planning, a total of 768 patients were seen in the first year. Oral contraception was dispensed for 377 patients and 187 intrauterine devices (IUCDs) were inserted; a further 204 IUCD patients attended only for follow-up visits. All side effects were adequately diagnosed by the nurse specialist.